Characteristics associated with early- vs. later-onset adult diabetes: The CARDIA study. (December 2021) - Cha, EunSeok; Pasquel, Francisco J.; Yan, Fengxia; Jacobs, David R.; Dunbar, Sandra B.; Umpierrez, Guillermo; Choi, Yuni; Shikany, James M.; Bancks, Michael P.; Reis, Jared P.; Spezia Faulkner, Melissa
Abstract: Aims: Differences in risk profiles for individuals with early- (<40 years old) vs. later-onset (≥40 years old) diabetes were examined. Methods: A nested case-comparison study design using 30-year longitudinal data from the Coronary Artery Risk Development in Young Adults (CARDIA) study was used. Survey data (socio-demographics, family history, medical records, and lifestyle behaviors), obesity-related measures (body mass index, weight), blood pressure, and laboratory data (insulin, fasting glucose, 2-h glucose, and lipids) were used to examine progression patterns of diabetes development in those with early-onset vs. later-onset diabetes. Results: Of 605 participants, 120 were in early-onset group while 485 were in later-onset group. Early-onset group had a lower A Priori Diet Quality Score, but not statistically significant at baseline; however, the between-group difference became significant at the time that diabetes was first detected (p = 0.026). The physical activity intensity score consistently decreased from baseline to the development of diabetes in both the early- and later-onset groups. Early-onset group showed more dyslipidemia at baseline and at the time that diabetes was first detected, and rapid weight gain from baseline to the development of diabetes. Conclusions: Emphases on lifestyle modification and risk-based diabetes screening in asymptomatic young adults are necessary for early detection and prevention.